2018
DOI: 10.1021/acs.nanolett.8b02005
|View full text |Cite
|
Sign up to set email alerts
|

Ultranarrow Second-Harmonic Resonances in Hybrid Plasmon-Fiber Cavities

Abstract: We demonstrate second-harmonic generation with ultranarrow resonances in hybrid plasmon-fiber cavities, formed by depositing single-crystalline gold nanorods onto the surface of tapered microfibers with diameters in the range of 1.7-1.8 μm. The localized surface plasmon mode of the single gold nanorod efficiently couples with a whispering gallery mode of the fiber, resulting in a very narrow hybrid plasmon-fiber resonance with a high quality factor Q of up to 250. When illuminated with a tunable 100 fs laser, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…This opens up new possibilities in applications based on collective plasmonic coupling such as lasing, 45,46 photovoltaics, 47 sensing, 48 and higher harmonic plasmonics. 11…”
Section: Resultsmentioning
confidence: 99%
“…This opens up new possibilities in applications based on collective plasmonic coupling such as lasing, 45,46 photovoltaics, 47 sensing, 48 and higher harmonic plasmonics. 11…”
Section: Resultsmentioning
confidence: 99%
“…2(b)). Here the linewidth is larger than that of hybrid Au NR and silica microfiber structure [22,23] due to the relatively larger optical loss of the polymer microfiber and the deviation of the NR orientation from vertical direction with respect to the microfiber length. Then the hybrid Au NR/PAM structure was placed in an airtight chamber with controllable humidity inside.…”
Section: Single-cavity-based Optical Rh Sensormentioning
confidence: 86%
“…Recently, it is found that, a plasmonic Au nanorod (NR) deposited on the surface of a microfiber can excite whispering gallery modes (WGMs) in the cross-section of the microfiber with diameter < 10 μm, and generate narrow-band localized surface plasmon resonance (LSPR) via strong coupling between the WGM and the LSPR modes [22], offering an opportunity for microfiber-based light-matter interaction on a smaller scale [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, using amorphous glass microcavities to generate lasers with RE‐ions has been well established . Furthermore, various kinds of lasers, such as Raman lasers and second harmonics, have been developed by applying glass WGM resonators. However, unlike crystals, glasses are amorphous, and they are characterized by relatively large phonon energy and broad phonon energy distribution, which are detrimental to the luminescence of rare earth (RE) ions that serve as the emission centers.…”
mentioning
confidence: 99%